Associations of Evangelical Christians-Baptists in Tatar ASSR during 1960s – 1980s - Fazliev, Aivaz M.; Ibragimov, Ruslan R.; Brodovskaya, Lyudmila N.; Samatova, Chulpan H. (Journal of History Culture and Art Research, 2017)
The relevance of the problem under study is caused by multi-confessional character of Russian society and the need of power to take into account the specific features of each confession in its religious policy. In order to understand the essential characteristics of contemporary issues in the state-confessional and inter-confessional relations the events and the processes taking place in the atheist Soviet past should be examined carefully. The purpose of the article is to study the specifics of the relationship between the authorities and associations of Evangelical Christians-Baptists during 1960s – 1980s, using the example of such a multi-confessional region as Tatarstan. The leading approach to the study of this problem was the civilizational approach, which enabled a comprehensive study of the object under study. The main results of the study are the studying of Tatar ASSR Baptist association forms and ways in the context of Soviet political and legal realities. The materials of the article can be useful in the preparation of educational literature, as well as in the practical activities of state structures implementing the policy in the spiritual sphere.